Analysis of Information Technology-Based Teaching Materials in Islamic Education Subjects at MA Islamiyah Sunggal - Ali Akbar (UMSU, 2022)
The research was conducted to analyze the information and communication technology utilization in MAS Islamiyah Sunggal during the learning process. The researcher found the results of the study that the MAS Islamiyah Sunggal school did not optimally use information and communication technology as a medium of teaching materials in the teaching and learning process with the limitations of the projector and the effectiveness of the old method with question and answer, discussion and problem-solving strategies, as well as prayer practice which does not require technology in practice. Because each teacher has their own plan of teaching and learning process, the school only provides facilities with 25 computers, 1 projector, and an LCD projector, which are used alternately by each class at MAS Islamiyah Sunggal.